Increasing Prevalence of Methicillin-Resistant Staphylococcus aureus Causing Nosocomial Infections at a University Hospital in Taiwan from 1986 to 2001 - Hsueh, Po-Ren (American Society for Microbiology, 2004)
A rapid emergence of nosocomial methicillin-resistant Staphylococcus aureus (MRSA) infection (from 26.3% in 1986 to 77% in 2001) was found. The susceptibility of 200 nonduplicate blood isolates of MRSA and 100 MRSA isolates causing refractory bacteremia to 22 antimicrobial agents disclosed that glycopeptides, quinupristin-dalfopristin, and linezolid remained the most active agents.